2003
DOI: 10.1161/01.str.0000056944.42686.1e
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement and Tissue-Type Plasminogen Activator for Acute Ischemic Stroke

Abstract: Background and Purpose— A systematic audit of intravenous tissue-type plasminogen activator (tPA) use and stroke outcomes in Cleveland, Ohio, during 1997–1998 demonstrated higher rates of symptomatic intracranial hemorrhage (ICH) than reported in the National Institute of Neurological Disorders and Stroke (NINDS) trial. We now report updated results of intravenous tPA use in the Cleveland Clinic Health System (CCHS). Methods— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(107 citation statements)
references
References 9 publications
7
99
0
Order By: Relevance
“…3,4 Nevertheless, only a minority of patients who present with acute ischemic stroke are treated with tPA. [5][6][7][8][9][10][11] One factor that may contribute to this low rate is clinician concern about the safety of the treatment. 12 Because the prospective trials evaluating this therapy were conducted at academic and community hospitals with institutional commitment to stroke care, relatively little data are available regarding the safety of thrombolysis as it is used in a broad range of hospitals in the community.…”
Section: Ntravenous Treatment With Tissue Plasminogen Activator (Tpa)mentioning
confidence: 99%
“…3,4 Nevertheless, only a minority of patients who present with acute ischemic stroke are treated with tPA. [5][6][7][8][9][10][11] One factor that may contribute to this low rate is clinician concern about the safety of the treatment. 12 Because the prospective trials evaluating this therapy were conducted at academic and community hospitals with institutional commitment to stroke care, relatively little data are available regarding the safety of thrombolysis as it is used in a broad range of hospitals in the community.…”
Section: Ntravenous Treatment With Tissue Plasminogen Activator (Tpa)mentioning
confidence: 99%
“…34,35 Reassuringly, studies have shown that with training and implementation of stroke teams, complication rates return to expected and acceptable levels. 36 National guidelines from the American College of Emergency Physicians recommend that hospitals alert local emergency medical systems regarding their stroke treatment readiness so that optimal routing of patients with suspected stroke to appropriate facilities may be implemented.…”
Section: Acute Stroke Treatment Including the Hyperacute And Emergenmentioning
confidence: 99%
“…2 Symptomatic ICH occurs in about 2% of controls but 7% of treated patients (up to 22% in less strictly controlled community studies). 17,21,22 The case for thrombolysis is a "house of cards" resting on two weak RCTs. Let's be honest; the overwhelming majority of hard evidence shows no benefit, yet the risk of harm is clear.…”
mentioning
confidence: 99%